HUBUNGAN ANTARA KESEGARAN JASMANI DENGAN HASIL BELAJAR PADA SDN 24 TANJUNG LEBAN KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Eli Fitria; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT This study is a correlational study by comparing the measurement results of two different variables. This study aims to determine any linkage Physical Fitness With Elementary School Student Results 24 Tanjung Leban Bukit Batu subdistrict Bengkalis, in this study a sample of the entire population of the male Class V students of SD Negeri 24 Tanjung Leban Bukit Batu subdistrict Bengkalis with a total of 22 people. Based on the research that has been conducted Sample Elementary School Grade V 24 Tanjung Leban Bukit Batu subdistrict Bengkalis that follow to determine the extent of the relationship between relationship Physical Fitness With Learning Outcomes students, rhitung = 0.511. At the significance level of 5% found rtabel = 0.423. thus rhitung> rtabel or 0.508> 0.423. This shows a correlation between the variables X and Y, or no significant relationship between physical fitness of students with learning outcomes V Elementary School Grade 24 Tanjung Leban Bukit Batu subdistrict Bengkalis. From the results of the calculation are known t = 2.66, while t table with df = n-2 = 22-2 = 20 at 95% confidence level is 1.725. then t> t table, 2.64> 1,725 thus null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is "The presence of a significant relationship between physical fitness by learning outcomes V Elementary School Grade 24 Tanjung Leban Bukit Batu subdistrict Bengkalis" accepted.Keywords : physical fitness, Learning Outcomes